Impact of pre-plasma on fast electron generation and transport from short pulse, high intensity lasers. (2nd December 2015) - Peebles, J.; McGuffey, C.; Krauland, C.M.; Jarrott, L.C.; Sorokovikova, A.; Wei, M.S.; Park, J.; Chen, H.; McLean, H.S.; Wagner, C.; Spinks, M.; Gaul, E.W.; et al.
Abstract: Previous experiments and modeling examining the impact of an underdense, pre-formed plasma in laser-plasma interactions have shown that the fast electrons are generated with energies higher than predicted by ponderomotive scaling [004, 003 –014 ]. We report on experiments using the Texas Petawatt high intensity (150 fs, 1.5 × 10 20 W cm −2 ) laser pulse, which were conducted to examine the mechanism for accelerating these high energy electrons. These experiments gauge the impact a controlled low density pre-formed plasma has on electron generation with a shorter time scale than previous experiments, 150–180 fs. Electron temperatures measured via magnetic spectrometer on experiment were found to be independent of preformed plasma. Supplemental computational results using 1D PIC simulations predict that super-ponderomotive electrons are generated inside a potential well in the pre-plasma [001 ]. However, while the potential well is established around 150 fs, the electrons require at least an additional 50 fs to be trapped and heated inside it.